Terapia Ocupacional e Educação: as proposições de terapeutas ocupacionais na e para a Escola - Pereira, Beatriz Prado (2018)
According to a current definition in Brazil, occupational therapy is a field of knowledge and intervention in health, education and in the social sphere, which brings together technologies and resources oriented to the emancipation and autonomy of people who have difficulty to insertion and participation in social life due to various and different problems. If we start from the conception that the occupational therapist's role in society is to worry about problems for which his knowledge and formation can contribute to the construction of solutions, which also happens in the field of education, it is important to discuss the themes of inclusive education, special education, and public school. The research that integrates this thesis has turned to occupational therapy and its interface with education, with the purpose of bringing together and understanding the propositions that occupational therapists have been doing for and in the "School". The question was how occupational therapists understand and consider (or not) school as a social institution that has been historically ambiguous and contradictory to deal with social inequalities, also being a source of social exclusion. Besides that in how occupational therapists position them selves in relation to school processes and about what assumptions will propose interventions and direct their attention in this field of science and practice. To answer these questions, some texts were initially collected, got together and systematized in the format of articles, searched through the combination of the descriptors: "occupational therapy" AND "school" and related versions in portuguese. Until April 2016, foreign articles were collected on the online databases of Web of Science and Scopus, with 1.265 texts found, whose titles, abstracts and keywords were read and analyzed for the application of exclusion and inclusion criteria that allowed the selection of 155 texts for reading in full. The selection of the national articles has made use of two ways, namely the SciELO online library - Scientific Electronic Library Online and the main national journals of the area: Cadernos de Terapia Ocupacional da UFSCar and Revista de Terapia Ocupacional da USP, bringing together a total of 31 texts for reading in full. In a second moment of the research, with the intention of raising occupational therapists involved with research and academic production in relation to the proposed theme, we opted to consult the Portal of the Directory of Research Groups in Brazil –CNPq, about groups of research in occupational therapy. After reading the names of the 57 groups found (January 2017), descriptions of their impacts and the objectives of the research lines that presented the interface between occupational therapy and education and/or school, six groups were selected, totaling 10 occupational therapists leading researchers or vice leaders. The curriculum of these researchers were consulted in the Plataforma Lattes of CNPq in order to verify and bringing together their academic productions in relation to the theme on the screen, allowing to choose among those with the most academic production, six occupational therapists leaders of the registered groups, the who were invited to collaborate with the research, in the form of an interview. All of them agreed to participate, and six individual interviews were made to talk about, discuss, question and reflect about their personal and academic trajectories for occupational therapy, on how they construct dialogue with education and on their perspectives about the theme. The data collected by the material composed of national and foreign articles, as well as the interviews, were organized into five thematic axes in order to delimit the theoretical arguments used to support and problematize the proposals of the occupational therapy and the dialogue with the field of education in the schools, namely: 1) The proposals of the occupational therapy for the field of education in the school: the foreign productions; 2) Social inclusion, school inclusion, the children with disabilities and the dialogue with occupational therapy; 3) Resources and devices for the practice of the occupational therapy in the school; 4) Child education, the child development and its interface with occupational therapy; 5) Childhood, adolescence and youths in situation of social vulnerability, the public school and occupational therapy. The main results of this work demonstrate that the therapeutic occupational intervention considers the school as a relevant social equipment that allows the access of popular groups to social visibility, educational experiences, cultural and/or, still, make possible better living conditions. However, their perspective has been placed on the construction of care processes shaped by the practice of health care, with a clinical logic with individual mechanisms of care. Taking the history of education and schooling, as well as its reality in the twenty-first century in Brazil, there is a need for a displacement that gives new contours to this practice, which must recognize that the participatory and social dimension of life, focus of attention in occupational therapy, is not reducible to the individual and private sphere of everyday school issues and/or problems.In this context, we believe that the moment is for the transformation of ideas, which need to consider in a differentiated way the teaching and learning process and the role of the school in front of the human formation, being aware of the limits of the school and acting on the possibilities and demands that it and the people who are in it, and/or who they want/should be present to occupational therapists.